Unfinished business : a regional education laboratory retrospective on school improvement - Egelson, Pauline; Bingham, Charles Steven; Howard, Barbara B. (Emerald Publishing Limited : Information Age Publishing, Inc., 2024)
"Unfinished Business A Regional Education Laboratory Retrospective on School Improvement is authored by education professionals who were once employed at one of the ten US federally funded education research and development laboratories, SERVE comprised of Alabama, Florida, Georgia, Mississippi, North Carolina, South Carolina. The school improvement recollections found in this book sprung not from authors' minds alone but were supported with facts, evidence, and research and literature, including interviews and evidence from former clients and collaborators. Each of the book authors wrote at least one chapter about a school improvement initiative that they were part of. Compared to the other nine labs, SERVE was heavily field based. SERVEs projects and publications focused on school improvement, research, policy, and professional development. The work was typically launched in a spirit best described as emergent design. Building on extant research and best practice, potential clients across the six-state region were approached with ideas for educational interventions and evidence to support theories of action. It is underscored that improving Americas public schools and the teachers and principals who lead them is a continuous process and difficult work. It is hoped that this book will offer suggestions to educators about how to implement school improvement, what works and what doesn't, and how initiatives can and do evolve positively and have an impact over time"--